KOMODIFIKASI FOMO DALAM STRATEGI PEMASARAN DIGITAL - Gita Pebiola; Andi Azhar (UM. Bengkulu, 2026)
This study aims to analyze the practice of commodifying Fear of Missing Out (FOMO) in the digital marketing strategies of Somtam Bengkulu MSMEs. The phenomenon of FOMO, defined as consumers' anxiety about missing out on experiences or benefits, has been utilized as an economic tool through tactics of scarcity, urgency, exclusivity, and social proof. This research employs a qualitative approach using the netnography method developed by Kozinets, which allows researchers to naturally observe interactions and culture in digital spaces. Data collection was conducted through online participatory observation, digital content analysis, and documentation on three social media platforms (Instagram, Facebook, and TikTok) over a two-month period, with data analysis using the interactive model of Miles, Huberman, and Saldaña, assisted by NVivo 12 Plus software. The findings reveal that Somtam Bengkulu implements all four dimensions of FOMO commodification in an integrated manner, with manifestations contextually adapted across platforms: TikTok effectively generates purchase intention based on scarcity, Instagram excels in building recommendations based on social proof, and Facebook functions as a transactional space. The psychological mechanism of FOMO operates through three continuous stages: generating curiosity, reinforcement through social proof, and conversion into purchase intention. Another significant finding is the seamless and internalized integration of FOMO strategies with local cultural values, reflected in collective- oriented FOMO, trust-based pre-order systems, and the use of Bengkulu's distinctive dialect in digital interactions. This study offers a Contextual FOMO Commodification Model that integrates strategic, psychological, and cultural dimensions, and introduces the concepts of Cross-Platform FOMO Spiral, Participatory FOMO Commodification, and Hybrid FOMO. Practically, MSMEs can optimize FOMO strategies by considering the unique characteristics of each platform and local values as sources of ethical and sustainable competitive advantage. Keywords: FOMO Commodification, Digital Marketing, Netnography, MSMEs, Local Branding, Somtam Bengkulu